NATURAL ZEOLITES STANDARDIZATION AS THE COMMODITY TOWARDS QUALITY ASSURANCE FOR ITS INDUSTRIAL USAGES - Muta’alim Muta’alim (Jurnal Zeolit Indonesia, 2002)
The quality of zeolite deposits at some locations are not the same, whereas in its utilizations, such as the utilization for the fertilizer carriers, the standard quality of zeolite should be fulfilled, for instances the cation exchange capacity should have a minimum value of 120 meq/100 gram, particle size should be